2022
DOI: 10.3389/fbioe.2022.818905
|View full text |Cite
|
Sign up to set email alerts
|

DesA Prognostic Risk Model of LncRNAs in Patients With Acute Myeloid Leukaemia Based on TCGA Data

Abstract: Purpose: This study aimed to combine the clinical data of acute myeloid leukaemia (AML) from The Cancer Genome Atlas (TCGA) database to obtain prognosis-related biomarkers, construct a prognostic risk model using long non-coding RNAs (lncRNAs) in AML and help patients with AML make clinical treatment decisions.Methods: We analysed the transcriptional group information of 151 patients with AML obtained from TCGA and extracted the expressions of lncRNAs. According to the mutation frequency, the patients were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Consequently, unraveling the intricacies of AC011752.1 and similar biomarkers within the context of immunotherapy offers the promise of discerning patient responses and, in turn, refining the tailoring of individualized therapeutic regimens (53,54). Furthermore, AC008937.3, AC018809.2, AC023090.1, CDK6-AS1, and AC073534.2 were also found to feature prominently in prognostic assessments of lung cancer (55), bladder cancer (56), hepatocellular carcinoma (57), gastric cancer (58), and acute myeloid leukemia (59), further underscoring their relevance in disease progression predictions across diverse malignancies. Remaining MPTDNLs, while yielding limited information from existing research findings, harbor untapped potential for predictive value, warranting future investigation and exploration.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, unraveling the intricacies of AC011752.1 and similar biomarkers within the context of immunotherapy offers the promise of discerning patient responses and, in turn, refining the tailoring of individualized therapeutic regimens (53,54). Furthermore, AC008937.3, AC018809.2, AC023090.1, CDK6-AS1, and AC073534.2 were also found to feature prominently in prognostic assessments of lung cancer (55), bladder cancer (56), hepatocellular carcinoma (57), gastric cancer (58), and acute myeloid leukemia (59), further underscoring their relevance in disease progression predictions across diverse malignancies. Remaining MPTDNLs, while yielding limited information from existing research findings, harbor untapped potential for predictive value, warranting future investigation and exploration.…”
Section: Discussionmentioning
confidence: 98%
“…To evaluate the outcome more accurately and promote treatment decisions for BC patients, we constructed the prognostic signatures based on 7 CRLs using LASSO regression analysis. Among them, there is evidence that the expression pattern of AC073534.2 may indicate its role in acute myeloid leukemia and was associated with a favorable prognosis [ 41 ]. RAP2C-AS1 has been reported to be highly expressed in esophageal cancer and associated with an unfavorable prognosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of NGS technologies, more and more AML-related mechanisms have emerged, including the eventual contribution of long noncoding RNAs (lncRNAs) (Mer et al, 2018;Liu et al, 2019;Mishra et al, 2022). In fact, several studies have established lncRNA-based prognostic models for clinical characterization in AML patients (Zhao et al, 2021;Ding et al, 2022;Zhang et al, 2022). Independently, an association of HSPs (Li and Ge, 2021) and ferroptosis-related lncRNAs (Zheng et al, 2021) has been demonstrated in AML.…”
Section: Discussionmentioning
confidence: 99%